Potensi Makanan Tradisional Bolu Kemojo Sebagai Daya Tarik Wisata di Pekanbaru - Chaniago, M. Fadli; Lestari Nasution, Annio Indah; Nasution, Juliana (Universitas Labuhanbatu, 2023)
This study aims to determine (1) the potential of Bolu Kemojo as a tourist attraction in Pekanbaru, and (2) the implementation of SWOT analysis to the potential of Bolu Kemojo as traditional food to attracts tourists in Pekanbaru. This study usedÂ qualitative approach. The research subjects in this study were the owners of traditional Bolu Kemojo food shops and itâ€™s consumers. Data collection techniques in this study using the interview method, observation, and documentation. This study uses SWOT Analysis as data analysis technique. The results of the study stated that Bolu Kemojo has great potential as a tourist attraction in Pekanbaru, by reason of Bolu Kemojo is a traditional Malay food that is still dense of culture and becomes a culinary tourism destination in the traditional culinary category. The results of the IE (Internal-External) matrix for the Bolu Kemojo business in Pekanbaru are located in cell number 1, namely concentration through vertical Integration which indicates that the cake is in a strong condition. The results of the SWOT obtained are in quadrant I, namely a position that indicates a growing organization (growth). From the analysis that has been carried out, it is recommended that the Bolu KemojoÂ Business in Pekanbaru carry out an aggressive strategy, namely by optimizing Strengths and taking advantage of large Opportunities for business development.